The Effect of Educaplay Based on Game-Based Learning on Learning Interest and Participation in IPAS of Fourth-Grade Madrasah Ibtidaiyah Students - Aura Della Rahmawati; Risalul Ummah (BASICA, 2026)
This study aimed to examine the effect of Educaplay based on Game-Based Learning (GBL) on fourth-grade Madrasah Ibtidaiyah students’ learning interest and participation in IPAS. The research employed a quantitative approach with a quasi-experimental pretest–posttest control group design conducted from January to February 2026 at MI Darussalam, involving 50 students (25 experimental; 25 control). Data were collected through a learning interest questionnaire (α = 0.89), participation observation sheets (reliability = 0.87), and documentation. Data analysis included the Kolmogorov–Smirnov normality test, Levene’s homogeneity test, independent t-test, Mann–Whitney U test, N-Gain analysis, and effect size (Cohen’s d). The experimental group achieved significantly higher results than the control group. The mean learning interest score was 93.00 (SD = 4.330) in the experimental class and 76.80 (SD = 6.103) in the control class, with a significant difference, t(47) = 10.607; p = 0.000; d = 3.09 (very large effect). The N-Gain was 54.20% (moderate category according to Richard R. Hake, 1999) in the experimental group and 20.53% (low category) in the control group. Learning participation also differed significantly (U = 121.00; p = 0.000), with higher scores in the experimental class (M = 20.28) than in the control class (M = 16.24). Educaplay based on Game-Based Learning significantly improves learning interest and participation in IPAS. The findings imply that interactive digital game-based media can enhance affective engagement and active classroom involvement in elementary education.